The relationship between knowledge, to learn and the school: one epistemological process approach - Viana, Maria José Braga (Paidéia (Ribeirão Preto), 2002)
This article intends to discuss some contributions Bernard Charlot and Jean-Yves Rochex have given about the relationship with knowledge, learning and school. The authors establish an enlightening distinction between information, knowledge, learning, and defend the idea that the various objects of learning imply different types of subjects' activities. The relationship with the knowledge concept is central in such discussion, with the notion of relationship understood as the grouping of meanings and the space of the subject's activities inscribed at a time. Thus, mobilization, activity and meaning emerge as central notions in the relationship with knowledge, and the problem of mobilization at the school is discussed considering the fact that there are different forms of relationship with the process of learning. It is established the hypothesis that an important part of school mobilization and success possibility is constituted before and outside the experience of the formal school itself. One example is the production of meaning witch is attributed to the formal school and which is, many times, produced in the context of the family.